The new political economy of disability transnational networks and individualised funding in the age of neoliberalism - Van Toorn, Georgia (London : Routledge, 2021)
This book addresses the ways in which individualised, market-based models of disability support provision have been mobilised in and across different countries through cross-national investigation of individualised funding (IF) as an object of neoliberal policy mobility. Combining rich theoretical and interdisciplinary perspectives with extensive empirical research, the book provides a timely examination of the policy processes and mechanisms driving the spread of IF amongst countries at the forefront of disability policy reform. It is argued that IF's mobility is not attributable to neoliberalism alone but to the complex intersections between neoliberal and emancipatory agendas and to the transnational networks that have blended the two agendas in new ways in different institutional contexts. The book shows how disability rights struggles have synchronised with neoliberal agendas, which explains IF's propensity to move and mutate between different jurisdictions. Featuring first-hand accounts of the activists and advocates engaged in these struggles, the book illuminates the consequences and risks of the dangerous liaisons and political trade-offs that seemed necessary to get individualised funding on the policy agenda for disabled people. It will be of interest to all scholars and students working in disability studies, social policy, sociology and political science more generally.
OCLC-licensed vendor bibliographic record.
Keywords: People with disabilities -- Services for; People with disabilities -- Services for -- Finance; People with disabilities -- Government policy; SOCIAL SCIENCE / Handicapped; POLITICAL SCIENCE / Public Policy / Social Policy; SOCIAL SCIENCE / Human Services